Bahasa Inggris - Abdul Kadir Ismail (LP2M IAIN Sultan Amai Gorontalo, 2018)
Interference of Malay Manado Language in Formal Spoken Indonesian Language: â€œA Case Study at Indonesian Language Studies, Gorontalo State Universityâ€ .This research aims to elaborate the kinds of interference in Malay Manado Language toward Indonesian Language on studentsâ€™ speech in class discussion performance and to describe the most frequent of interference that students produced in class discussion performance by students in Indonesian Language Studies. Besides, the purpose of this research is to disclose the students deal with the interference on their speech in class discussion performance.The research was conducted in Indonesian Language Studies, Gorontalo State University. The data were collected from studentsâ€™ speech in class discussion performance by using recording technique. The samples were 30 respondents. Two methods in analyzing data, namely descriptive quantitative and qualitative methods. There are three kinds of interference that students produced on studentsâ€™ speech in class discussion performance namely phonological interference, morphological interference, and lexical interference. Firstly, in phonological interference can be categorized into assimilation, merger colescence or diftong, syncope, apocope, compression, and vowel modification. In morphological interference, they produced prefix addition, imperative form, reduplication, compounding form, and negation form. In Lexical interference, they created nine types of interference namely verb, noun, adjective, pronoun, adverb, question form, language particle, possesive, and preposition. Secondly, the most frequent type of interference on studentsâ€™ speech in class discussion performance is lexical interference. It is about 193 in the percentage 59.38 %. Lastly, there are some factors that causing interference on studentsâ€™ speech. They are, bilingualism, the lack of using Indonesian Language, needs for synonyms and the last is studentsâ€™ high prestige.